PERCEIVED CONTRIBUTIONS OF UKULELE ENSEMBLE LEARNING TO PEACE-LOVING CHARACTER: A QUALITATIVE REANALYSIS - Bella Kenzha Tahalele; Lisye Salamor; Titus Gaite (EDUCATIONE, 2026)
Peace-oriented character education requires school practices in which students repeatedly enact cooperation, emotional regulation, respect, and non-discrimination. This article presents a secondary qualitative reanalysis of an archival field report on ukulele learning in a public junior high school in Ambon, Indonesia. The available corpus comprised reported interview responses from six informants—the principal, one music teacher, and four students—originally collected on 7–8 May 2025; no new participant contact occurred, and undocumented observation references were treated only as contextual description. All available excerpts were anonymized by role, coded for meaning units, compared across informant groups, and interpreted through peace-education, music-education, and locally situated pedagogy literature. Participants associated ukulele learning with four interconnected processes: disciplined and constructive engagement; cooperation, peer assistance, and non-discrimination during ensemble work; local cultural belonging and heritage interest; and sharing practices prompted by unequal access to instruments. The findings support a provisional pedagogical-ecology model in which structured rehearsal, teacher modeling, peer interdependence, local meaning, and equitable access jointly shape perceived character learning. The evidence does not demonstrate causal behavioral change because the archival report lacked raw transcripts, systematic observations, comparison data, and verified ethics documentation. Schools may use the model as a design proposition rather than a proven intervention. Future research should employ prospective multisite designs, direct observation, broader participant groups, and documented consent procedures.